Rapid response mechanism in conflict-affected settings of Cameroon: lessons learned from a multisector intervention for internally displaced persons - Lundi-Anne Omam; Alain Metuge (Inishmore Laser Scientific Publishing Ltd, 2023)
The Northwest and Southwest regions of Cameroon have experienced armed conflict over the last seven years, characterized by mass displacement and limited access to health care and social amenities. In response, an emergency intervention programme called "rapid response mechanism" (RRM) was initiated to provide lifesaving services to internally displaced persons. The intervention was multisectoral and included a health component, nutrition, water hygiene and sanitation, and child protection. RRM served communities of Ekondo Titi district, marked with high levels of insecurity, poor telecommunication networks and limited geographical access. Although the RRM was designed to provide rapid and lifesaving interventions to the affected populations; the RRM, in this case, was only initiated one year after the conflict escalated. Key benefits of the RRM included: (i) increased access to health care services through its integrated community case management approach, (ii) development of full displacement map within the health district, further strengthening the health system by establishing a community-based surveillance and response system through community health workers, and (iii) assisting the health district team in mass vaccination campaigns in seven of the nine health areas, which were otherwise completely inaccessible. The RRM model was largely primary health care focused compared to other RRMs in conflict-affected countries. It is important for RRM benefit packages to be harmonized to enable better preparedness and responses in conflicts. There is also a need for better coordination among sectoral partners to ensure improved response in crises.